Draft genome sequence of a bovine enterovirus isolate recovered from sewage in Nigeria (2018)
We describe the draft genome of a bovine enterovirus (EV) isolate recovered from sewage in Nigeria. This isolate replicates on both RD and L20B cell lines but is negative for all EV screens in use by the Global Poliovirus Eradication Initiative (GPEI). It contains 7,368 nucleotides (nt) with 50.2% G C content and an open reading frame (ORF) with 6,525 nt (2,174 amino acids).